Saudosa Maloca, Maloca querida: um estudo morfológico da relação forma/usos do espaço em moradias autoconstruídas e construídas pelo poder público após um ano de ocupação - Farias, Suerda Ivanete Gomes de (2004)
This study intends to enhance the existing knowledge concerning the patterns of the uses of space for low cost housing in Parnamirim, Rio Grande do Norte, Brazil, by way of comparative morphological studies in spatial arrangements and articulations regarding three distinct, however inter-related, sets of social housing: (1) a development comprising 21 self-built houses erected on public routes and illegal plots within a tract of land originally designed to be an industrial development: (2) architect-designed houses built by the public authority in order to accommodate the previous 21 (plus a few additions) families occupying the self-built dwellings, and (3) modifications performed by dwellers on a total of those 24 houses built by the public authority after an occupation period of one year. The predominant uses of each room within the self-built and modified houses were represented in ground plan, based on empirical observation, surveys with dwellers and the use of analytical procedures of morphologic analysis of nature predominantly geometric (specific) and topology (space syntax analysis). A scale of priorities was identified in relation to the uses of each room, its geometrical arrangement (adjacency, front/back relations etc), and underlying structures (connectivity, depth and spatial integration) in order to establish congruencies and non-congruencies between a social-cultural order embedded in the self-built domestic space and the design logic contained in the houses offered by official agencies. The comparative analysis points towards the convivial existence of two tendencies: one that seems to reinforce a design logic inasmuch as the additions and modifications performed by the dwellers do not alter but even emphasize the original configuration of the designed houses, and another one in which those patterns are subverted in accordance with a logic which, to a lesser or greater degree, coincides with that of the self-built dwellings